Developing Kemukus Mountain Flipbook Integrated with TaRL Approach in Improving Students’ Comprehension of Descriptive Texts - Setiyani, Tasya Novi; Purwati, Panca Dewi (Journal of Languages and Language Teaching, 2025)
Teachers have not optimally used technology-based learning media and have not implemented a Teaching at the Right Level-based learning approach. causing students' understanding of descriptive text to be low. This study aims to develop, test the feasibility, and effectiveness of Teaching at the Right Level-based flipbook learning media to improve the understanding of fifth grade students. This type of research is research and development with the Borg and Gall model. The subjects of this study were 30 fifth grade Elementary students. Data collection techniques used tests (pretest and posttest) and non-tests (observation, interview, questionnaire). Data analysis techniques using normality test, t test and N-Gain test. The results showed: (1) Teaching at the Right Level-based flipbooks were developed using the canva application; (2) the results of the validity test of material experts, media experts, teachers, and students received a very feasible category; (3) effectiveness is shown from the results of analy-ing pretest and posttest scores. The results of the t test get a sig. (2-tailed) value of 0.00 <0.005. The conclusion in this studv shows that the development of learning media flipbooks based on Teaching at the Right Level was successfully developed, very feasible, and effectively used to improve the understanding of descriptive text for fifth grade Elementary students.